Flow Field and Performance Study of Vertical Axis Savonius Type SST Wind Turbine. (March 2017) - Al-Faruk, Abdullah; Sharifian, Ahmad
Abstract: It has been suggested that waste heats or naturally available heat sources can be utilized to produce swirling flow by a design similar to that of split channels which is currently used to initiate fire whirls in laboratories. A new hybrid power system has been proposed combining the conventional Savonius wind turbine and split channel mechanisms. Previous computational and experimental works indicate a performance improvement in the new hybrid design (named as swirling Savonius turbine, SST) compared to the conventional Savonius turbine. However, the lack of detailed descriptions of the flow field around the swirling Savonius turbine inhibits complete understanding of performance of the hybrid power system. The aim of this study is to numerically explore the three-dimensional unsteady flow around the rotor, and develop a simulation method for predicting their aerodynamic performance using control volume based CFD package of ANSYS CFX. Sliding mesh feature of CFX allowed to solve the motion of the moving blades. Numerical simulations results of SST were compared with the experimental results. A discussion on the detailed flow field characteristics, including velocity vector, velocity streamlines, pressure distribution, vorticity analysis, and examination of power and torque coefficients behavior are presented.